Getting High After Getting Out: understanding the Relationship Between Support, Stressors, and Drug Use Among Men and Women in Early Reentry - Griffin, Amber D. (Crime & delinquency, 2020)
This study uses data from the Serious and Violent Offender Reentry Initiative (SVORI) to examine the effects of social support and stressors on self-reported illicit drug use among 1,074 recently released individuals (men = 874; women = 200). Three broad conclusions can be drawn from these findings: (a) Men were more likely than women to use drugs in the first 3 months following release from prison; (b) mental health and neighborhood quality were universal predictors of drug use in early reentry; and (c) social support, stressors, and individual and legal characteristics affected drug use for men and women differently. This work fills knowledge gaps related to the intersection of reentry, gender, and drug use within the context of correctional policy and practice.